Microbial community respiration kinetics and their dynamics in coastal seawater - Henry L.S. Cheung; Rachel L. Simister; Christelle Not; Sean A. Crowe (Science of The Total Environment, 2024)

Correction: Metal(loid)s Removal Response to the Seasonal Freeze–Thaw Cycle in Semi-passive Pilot Scale Bioreactors - Morgane Desmau; Rachel Simister; Susan A. Baldwin; Guillaume Nielsen (Mine Water and the Environment, 2024)

Metal(loid)s Removal Response to the Seasonal Freeze–Thaw Cycle in Semi-passive Pilot Scale Bioreactors - Morgane Desmau; Rachel Simister; Susan A. Baldwin; Guillaume Nielsen (Mine Water and the Environment, 2024)
There is an increasing demand for cost-effective semi-passive water treatment that can withstand challenging climatic conditions and effectively and sustainably manage mine-impacted water in (sub)arctic regions. This study investigated the ability of four pilot-scale bioreactors inoculated with locally sourced bacteria and affected by a freeze–thaw cycle to remove selenium and antimony. The bioreactors were operated at a Canadian (sub)arctic mine for a year. Two duplicate bioreactors were installed in a heated shed that was maintained at 5 °C over the winter, while two other duplicates were installed outdoors and left to freeze. The removal rate of selenium and antimony was monitored weekly, while a genomic characterization of the microbial populations in the bioreactors was performed monthly. The overall percentage of selenium and antimony removal was similar in the outside (10–93% Se, 20–96% Sb) and inside (35–94% Se, 10–95% Sb) bioreactors, apart from the spring thawing period when removal in the outdoor bioreactors was slightly lower for Se. The dominant taxonomic groups of microbial populations in all bioreactors were Bacteroidota, Firmicutes, Desulfobacterota and Proteobacteria. The microbial population composition was consistent and re-established quickly after spring thaw in the outside bioreactors. This demonstrated that the removal capacity of bioreactors inoculated with locally sourced bacteria was mostly unaffected by a freeze–thaw cycle, highlighting the strength of using local resources to design bioreactors in extreme climatic conditions.

Functional redundancy imparts process stability to acidic Fe( II )‐oxidizing microbial reactors - Diana Ayala‐Muñoz; Rachel L. Simister; Sean A. Crowe; Jennifer L. Macalady; William D. Burgos (Environmental Microbiology, 2021)
Summary In previous work, lab‐scale reactors designed to study microbial Fe(II) oxidation rates at low pH were found to have stable rates under a wide range of pH and Fe(II) concentrations. Since the stirred reactor environment eliminates many of the temporal and spatial variations that promote high diversity among microbial populations in nature, we were surprised that the reactors supported multiple taxa presumed to be autotrophic Fe(II) oxidizers based on their phylogeny. Metagenomic analyses of the reactor communities revealed differences in the metabolic potential of these taxa with respect to Fe(II) oxidation and carbon fixation pathways, acquisition of potentially growth‐limiting substrates and the ability to form biofilms. Our findings support the hypothesis that the long‐term co‐existence of multiple autotrophic Fe(II)‐oxidizing populations in the reactors are due to distinct metabolic potential that supports differential growth in response to limiting resources such as nitrogen, phosphorus and oxygen. Our data also highlight the role of biofilms in creating spatially distinct geochemical niches that enable the co‐existence of multiple taxa that occupy the same apparent metabolic niche when the system is viewed in bulk. The distribution of key metabolic functions across different co‐existing taxa supported functional redundancy and imparted process stability to these reactors.

Rates and Pathways of N2 Production in a Persistently Anoxic Fjord: Saanich Inlet, British Columbia - Céline C. Michiels; Julia A. Huggins; Karina E. Giesbrecht; Jenifer S. Spence; Rachel L. Simister; Diana E. Varela; Steven J. Hallam; Sean A. Crowe (Frontiers in Marine Science, 2019)

Thermal stress responses in the bacterial biosphere of the G reat B arrier R eef sponge, R hopaloeides odorabile - Rachel Simister; Michael W. Taylor; Peter Tsai; Lu Fan; Timothy J Bruxner; Mark L Crowe; Nicole Webster (Environmental Microbiology, 2012)
Summary Marine sponges are diverse, abundant and provide a crucial coupling point between benthic and pelagic habitats due to their high filtration rates. They also harbour extensive microbial communities, with many microbial phylotypes found exclusively in sponge hosts and not in the seawater or surrounding environment, i.e. so‐called sponge‐specific clusters ( SCs ) or sponge‐ and coral‐specific clusters ( SCCs ). We employed DNA (16 S rRNA gene) and RNA (16 S rRNA )‐based amplicon pyrosequencing to investigate the effects of sublethal thermal stress on the bacterial biosphere of the G reat B arrier R eef sponge R hopaloeides odorabile . A total of 8381 operational taxonomic units ( OTUs ) (97% sequence similarity) were identified, affiliated with 32 bacterial phyla from seawater samples, 23 bacterial phyla from sponge DNA extracts and 18 bacterial phyla from sponge RNA extracts. Sublethal thermal stress (31° C ) had no effect on the present and/or active portions of the R. odorabile bacterial community but a shift in the bacterial assemblage was observed in necrotic sponges. Over two‐thirds of DNA and RNA sequences could be assigned to previously defined SCs / SCCs in healthy sponges whereas only 12% of reads from necrotic sponges could be assigned to SCs / SCCs . A rapid decline in host health over a 1° C temperature increment suggests that sponges such as R . odorabile may be highly vulnerable to the effects of global climate change.

Sponge‐specific clusters revisited: a comprehensive phylogeny of sponge‐associated microorganisms - Rachel L. Simister; Peter Deines; Emmanuelle S. Botté; Nicole S. Webster; Michael W. Taylor (Environmental Microbiology, 2012)
Summary Marine sponges often contain diverse and abundant communities of microorganisms including bacteria, archaea and eukaryotic microbes. Numerous 16S rRNA‐based studies have identified putative ‘sponge‐specific’ microbes that are apparently absent from seawater and other (non‐sponge) marine habitats. With more than 7500 sponge‐derived rRNA sequences (from clone, isolate and denaturing gradient gel electrophoresis data) now publicly available, we sought to determine whether the current notion of sponge‐specific sequence clusters remains valid. Comprehensive phylogenetic analyses were performed on the 7546 sponge‐derived 16S and 18S rRNA sequences that were publicly available in early 2010. Overall, 27% of all sequences fell into monophyletic, sponge‐specific sequence clusters. Such clusters were particularly well represented among the Chloroflexi , Cyanobacteria , ‘ Poribacteria ’, Betaproteobacteria and Acidobacteria , and in total were identified in at least 14 bacterial phyla, as well as the Archaea and fungi. The largest sponge‐specific cluster, representing the cyanobacterium ‘ Synechococcus spongiarum ’, contained 245 sequences from 40 sponge species. These results strongly support the existence of sponge‐specific microbes and provide a suitable framework for future studies of rare and abundant sponge symbionts, both of which can now be studied using next‐generation sequencing technologies.